UPAYA MENINGKATKAN HASIL BELAJAR MENGGUNAKAN MODEL PBL BERBASIS ETNOMATIKA: Array - Fauriza Tahta Alfiatusya'diyah; Agung Setyawan (eductum: Jurnal Literasi Pendidikan, 2022)
The research has the aim of improving student learning outcomes before and after applying the ethnomathematic based PBL model in mathematics lessons. This research was conducted at SDN Juwet Kenongo, Porong District, Sidoarjo Regency. The type of research used is classroom action research (PTK). The method used in this study was a research by Kemmis and Taggart which used a spiral system cycle consisting of planning, action, observation, and reflection. The sample in this study were students of class V as many as 14 students. The research instrument used observation sheets, interviews, and questionnaires with evaluation tests. For quantitative data analysis, it is processed using statistical formulas, while qualitative data analysis is carried out by describing all available data from the observation sheet. The results showed that the mathematics learning outcomes of students using the ethnomatematic based PBL model in class V had increased. It is shown that the average grade V mathematics learning outcomes are 50% and the results of the observation data analysis are 80% because learning using the PBL model can improve student mathematics learning outcomes, so it is hoped that the teacher can apply the learning